2005
DOI: 10.1007/s10462-004-5900-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Dynamic Multi-Objective Optimization Problems with Objective Replacement

Abstract: This paper studies the strategies for multi-objective optimization in a dynamic environment. In particular, we focus on problems with objective replacement, where some objectives may be replaced with new objectives during evolution. It is shown that the Pareto-optimal sets before and after the objective replacement share some common members. Based on this observation, we suggest the inheritance strategy. When objective replacement occurs, this strategy selects good chromosomes according to the new objective se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Guan et al [2005] suggested creating DMOOPs by replacing objective functions with new objective functions over time. The advantage of Guan et al's approach is that the new objective function(s) can cause a severe change in the DMOOP, and by selecting the objective functions carefully, various types of changes can be incorporated into the DMOOP.…”
Section: Dmoo Benchmark Functions Currently Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Guan et al [2005] suggested creating DMOOPs by replacing objective functions with new objective functions over time. The advantage of Guan et al's approach is that the new objective function(s) can cause a severe change in the DMOOP, and by selecting the objective functions carefully, various types of changes can be incorporated into the DMOOP.…”
Section: Dmoo Benchmark Functions Currently Usedmentioning
confidence: 99%
“…When objective functions are changed over time, as in the approaches followed by Guan et al [2005] and Wang and Li, the objective functions should be selected carefully to ensure that the resulting objective functions hinder the algorithm in finding the POF in various ways, as discussed in Section 3. Another approach was followed by Jin and Sendhoff [2004], where a two-objective DMOOP is constructed from a three-objective MOO function.…”
Section: Dmoo Benchmark Functions Currently Usedmentioning
confidence: 99%
“…Guan et al [28] introduced a set coverage measure that is based on the S and D metrics introduced by Zitzler [71]. The HV of the objective space that is dominated by POF * but not by POF ′ , referred to as the D-metric, is defined as…”
Section: Set Coverage Metricmentioning
confidence: 99%
“…An approach to reformulate a three-objective optimisation test function to define a dynamic two-objective optimisation problem was presented by Jin and Sendhof [14]. Guan et al [11] presented an approach to create DMOOPs by replacing objective functions with new ones at specific times. DMOOPs based on the static MOO twoobjective ZDT functions [26] and the scalable DTLZ functions [5] was presented by Farina et al [7].…”
Section: Dynamic Multi-objective Optimization Issuesmentioning
confidence: 99%